Impact of Treviamet® & Treviamet XR® on quality of life besides glycemic control in type 2 DM patients - Asima Khan; Muhammad Adnan Kanpurwala; Riasat Ali Khan; Najum F. Mahmudi; Verumal Lohano; Shakeel Ahmed; Majid Khan; Fareed Uddin; Syed Mohammad Ali; Maliha Saghir; Syed Hussain Baqar Abidi; Jahanzeb Kamal (BMC Endocrine Disorders, 2023)
Abstract Background Maintaining the quality of life is the main objective of managing type 2 diabetes (T2DM) (QoL). Since it is a key factor in patient motivation and adherence, treatment-related QoL has always been considered when choosing glucose-lowering medicines. The objective of the study was to evaluate the quality of life besides glycemic control among type 2 diabetes mellitus patients receiving Treviamet® & Treviamet XR® (Sitagliptin with Metformin) in routine care. Methods It was a prospective, open-label, non-randomized clinical trial including T2DM patients uncontrolled on Metformin therapy. All patients received Treviamet® & Treviamet XR® for six months. Sequential changes in QoL, fasting plasma glucose, HbA1c, body weight, and blood pressure were monitored from baseline to 3 consecutive follow-up visits. The frequency of adverse events (AEs) was also noted throughout the study. Results A total of 504 patients were screened; 188 completed all three follow-ups. The mean QoL score significantly declined from 57.09% at baseline to 33.64% at the 3rd follow-up visit (p < 0.01). Moreover, a significant decline in mean HbA1c and FPG levels was observed from baseline to 3rd follow-up visit (p < 0.01). Minor adverse events were observed, including abdominal discomfort, nausea, flatulence, and indigestion. Gender, HbA1c, diarrhea, and abdominal discomfort were significant predictors of a patient’s QoL, as revealed by the Linear Regression Model (R2 = 0.265, F(16, 99) = 2.231). Conclusion Treviamet® & Treviamet XR® significantly improved glycemic control (HbA1c levels) and QoL in T2DM patients without serious adverse events. Trial registration ClinicalTrials.gov identifier (NCT05167513), Date of registration: December 22, 2021.